Topic and language specific internet search engine - Tikk Domonkos (Acta cybernetica, 2007)
In this paper we present the result of our project that aims to build a categorization-based topic-oriented Internet search engine. Particularly, we focus on the economic related electronic materials available on the Internet in Hungarian. We present our search service that harvests, stores and makes searchable the publicly available contents of the subject domain. The paper describes the search facilities and the structure of the implemented system with special emphasis on intelligent search algorithms and document processing methods.